ANTHROPOMETRIC CHARACTERISTICS AND HEALTH SELF-ASSESSMENT OF FEMALE UNIVERSITY STUDENTS - Pilipović-Spasojević, Olivera; Ponorac, Nenad; Spremo, Mira; Radojčić, Tina (Scripta Medica, 2020)
Background/Aim: An important period in becoming a young woman is studying at the University. It is a period of taking responsibility for yourself, your health and social relationships. The abilities formed during this period directly affect one’s physical and mental health. The study was undertaken in order to determine anthropometric characteristics and to evaluate the health of female students aged 19 to 22 at the University of Banja Luka. Methods: An analytical population study based on a survey using a standardized SF36 self-report health test and measurement using an objective bioimpedance method with Omron BF 511 estimated 408 female students aged 19 to 22, based on inclusion criteria. Results. The mean body mass index (BMI) of female students was 22.1 ± 3.2 kg/m2, with 31.80 ± 6.47 percent fat and 28.15 ± 2.81 percent muscle mass. The mean values of the SF 36 for mental health (MH) questionnaires was 60.7 ± 24.95 and for physical health (FH)72.21 ± 25.89. Conclusion: Female students have ideal BMI values. Physical health self-assessment reach higher values than the mental health self-assessment, which is probably related to mental distress and problems during studying . Keywords: student health, anthropometry, SF36 questionnaire, physical and mental health,